2011
DOI: 10.1097/jpn.0b013e318226ee2c
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia in Very Preterm Infants

Abstract: Supplemental oxygen plays a critical role in the management of infants born at the lower limit of viability, but not without the risk of complications resulting from high levels or prolonged exposure. Longitudinal studies of very premature infants, born at less than 28 weeks' gestation, establish a clear relationship between pulse oximetry saturation readings above 92%, or hyperoxia, and development of severe retinopathy of prematurity, chronic lung disease, and brain injury. Hyperoxia is neither natural nor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…To further compound this hyperoxic insult, supplemental oxygen is frequently used in the resuscitation, care, and support of premature infants. While this respiratory support is necessary and beneficial to the neonate in the short term, it is not without risk to long term pulmonary health and is associated with significant morbidities (Bhandari 2010; Deuber and Terhaar 2011; Jobe and Kallapur 2010; Sola and Deulofeut 2006). …”
Section: Hyperoxia and The Developing Lungmentioning
confidence: 99%
See 1 more Smart Citation
“…To further compound this hyperoxic insult, supplemental oxygen is frequently used in the resuscitation, care, and support of premature infants. While this respiratory support is necessary and beneficial to the neonate in the short term, it is not without risk to long term pulmonary health and is associated with significant morbidities (Bhandari 2010; Deuber and Terhaar 2011; Jobe and Kallapur 2010; Sola and Deulofeut 2006). …”
Section: Hyperoxia and The Developing Lungmentioning
confidence: 99%
“…Bronchopulmonary dysplasia (BPD) has been the figurehead of hyperoxia-induced neonatal lung disease since first described by Northway et al in 1967 (Northway et al 1967). However, even infants who do not develop BPD have been shown to have long-term morbidities associated with preterm birth including increased susceptibility to respiratory infections, childhood wheezing, and childhood and adult asthma (Been et al 2014; Deuber and Terhaar 2011; Martin et al 2013; Pramana et al 2011; Vrijlandt et al 2013). Multiple animal and in vitro studies have demonstrated a possible contributing role for hyperoxic exposure in these airway pathologies (Belik et al 2003; Hartman et al 2012; O'Reilly et al 2014a; O'Reilly et al 2014b; Wang et al 2014).…”
Section: Hyperoxia and The Developing Lungmentioning
confidence: 99%
“…However, many authors recommend limitation of hyperoxia exposure in the newborn period due to increased awareness about its noxious effects [1][3]. Premature newborns, in particular, are known to be more susceptible to oxidative stress due to immaturity of the antioxidant system [4][5] and due to deficiency of antioxidant precursors in parenteral nutrition [6].…”
Section: Introductionmentioning
confidence: 99%
“…The goal of ventilator treatment is to balance gas exchange while minimising trauma to the lung tissue [3]. Adjusting oxygenation and ventilator therapy is challenging, and improved strategies are needed to minimise hyperoxemia [4] and hyperventilation with hypocarbia [5,6] in preterm and full-term newborns. Appropriate oxygenation is achieved by titrating the fraction of inspired oxygen (FiO 2 ) and the mean airway pressure (MAP).…”
Section: Introductionmentioning
confidence: 99%